Unveiling the Cosmic Dance of Repeated Nuclear Transient ASASSN-14ko: Insights from Multiwavelength Observations - Shifeng Huang; Tinggui Wang; Ning Jiang; Rong-Feng Shen; Zhaohao Chen; Yuanming Wang; Jiazheng Zhu; Yibo Wang; Yunguo Jiang; Xinwen Shu; Hucheng Ding; Xiongjun Fang; et al. (The Astrophysical Journal)
ASASSN-14ko is a periodically repeating nuclear transient. We conducted high-cadence, multiwavelength observations of this source, revealing several recurrent early bumps and rebrightenings in its UV/optical light curves. The energy released during these bumps and rebrightenings shows a diminishing trend in recent UV/optical outbursts, which we monitored through multiwavelength observations. These features can be ascribed to the interaction between stream debris and the expanded disk in the repeated partial tidal disruption event. The X-ray light curve exhibits an inverse pattern compared to the UV/optical bands, displaying sporadic outbursts. Furthermore, our observations demonstrate that the blackbody temperature and radius in each outburst increase with the UV/optical luminosity, and such evolution resembles that observed in X-ray quasiperiodic eruptions, distinguishing it from typical tidal disruption events.